THE ROLE OF THE TEAM IN ENSURING THE INDIVIDUAL AND HIS PSYCHOLOGICAL MATURITY (TAMADDUN NURI JURNALI, 2024)
The concept of psychological maturity of a personality is multifaceted and includes such basic concepts as cognitive processes, emotions and emotions, communication and relationships, abilities and temperament, volitional qualities and the degree of formation of his behavior, patterns, psychological mechanisms, states and processes.